SUSTAINABLE BUSINESS MODEL INNOVATION FOR SOCIAL ENTERPRISE (CASE STUDY: PT PASAREMPAH NUSANTARA LOHJINAWI) - Bernadetta Nurani; Prima Dwiratri (CV. Radja Publika, 2025)
The Negeri Rempah Foundation, a nonprofit organization, promotes awareness of Indonesia’s cultural diversity, particularly the historical spice trade, through its #JalurRempah campaign. Aligned with the Indonesian government’s initiative to nominate the Spice Route as a UNESCO World Cultural Heritage, the foundation initially focused on social and cultural impact. However, as it expanded into end-to-end business processes, challenges arose in balancing social impact with business development. To address this, the foundation transitioned into PT Pasarempah Nusantara Lohjinawi, a social enterprise ensuring sustainability while maintaining its social mission.This study examines the key factors for a successful transition, identifies challenges through gap analysis, and explores business models that balance financial and social objectives. Using a mixed-methods approach, data was gathered through interviews and surveys to evaluate the current business model. The Social Business Canvas Model was applied to bridge gaps and refine the framework. Key success factors included a mindset shift, a clear vision, and a structured organization aligned with regulations. The study proposes a new customer segmentation strategy to strengthen sustainability, market expansion, and social impact. The findings offer insights for other NGOs transitioning into social enterprises, with future research recommended on optimal organizational structures for such transformations.